2013
DOI: 10.1002/jor.22495
|View full text |Cite
|
Sign up to set email alerts
|

Release of growth factors from a reinforced collagen GAG matrix supplemented with platelet rich plasma: Influence on cultured human meniscal cells

Abstract: Damage to meniscal cartilage has been strongly linked to accelerated articular wear and consequently to osteoarthritis. Damage might be ameliorated by delivery of growth factors from platelet rich plasma (PRP) via a fiber reinforced collagen matrix designed for meniscal repair. PRP composition, release of growth factors, and influence on meniscal cell growth and gene expression were investigated. PRP was prepared using Harvest Smartprep (HS-PRP), Cascade Fibrinet (CF-PRP), and a simple centrifuge protocol (DC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…However, statistical tests performed before the experiment indicated that samples from a minimum of three independent sheep would yield results with adequate power. Our previous experimentation had also shown that this would be adequate, nevertheless more samples would have strengthened the data 26 . The other deficit of our experiment was a lack of qualitative information such as microscopy.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 77%
“…However, statistical tests performed before the experiment indicated that samples from a minimum of three independent sheep would yield results with adequate power. Our previous experimentation had also shown that this would be adequate, nevertheless more samples would have strengthened the data 26 . The other deficit of our experiment was a lack of qualitative information such as microscopy.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 77%
“…Recently, PRP composition, release of growth factors, and influence on meniscal cell growth and gene expression were investigated. Collagen matrix with PRP was able to increase meniscal cell number above peripheral whole blood and upregulated gene expression of aggrecan, collagen type I (a1), and elastin (Howard et al 2014). PRP combined with fiber-reinforced collagen matrix suggests to influence meniscal cells and might be of use for treating meniscal defects.…”
Section: Meniscal Pathologiesmentioning
confidence: 98%
“…Radial-longitudinal tears [173] Electro spun type I collagen scaffolds and vascular/avascular region meniscal cells Avascular meniscal tears [174] Radio opaque electro spun scaffold Meniscal regrowth [176] Wrapping of meniscal defects with collagen membrane and injection of MSCs Tears in avascular zone [156] Aligned electro spun nano fibrous scaffold Radial tear [178] Collagen gel scaffold or HA hydrogel delivery of meniscal, synovial and adipose cells Bucket handle tear [177] Type I collagen scaffold/ infrapatellar fat pad Anterior 2 mm round holes [179] Chondrocyte + PLGA mesh scaffold + PRP Chondrocytes evaluated [180] Meniscal cells in fibre reinforced collagen-GAG scaffold + PRP Gene profiling study [168]…”
Section: Scaffolds Lesion and Study Type Referencesmentioning
confidence: 99%
“…An alternative approach is the co-culture of MSCs with chondrocytes or meniscal cells to pre-condition these or expand cell numbers prior to their incorporation into bioscaffolds, hydrogels or bioadhesives prior to administration to the meniscal defect [159,164] (Figure 3a and b). Platelet rich plasma or platelet rich fibrin clots have been used to enhance meniscal repair in bioscaffolds [120,[165][166][167][168][169][170][171].…”
Section: Bioscaffolds Bioactive Substances and Bioadhesives And Menimentioning
confidence: 99%
See 1 more Smart Citation